2018
DOI: 10.1002/adfm.201801738
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Activatable Assembled Nanoparticles to Improve Tumor Penetration and Eradicate Metastasis in Triple Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a kind of aggressive malignancy with fast metastatic behavior. Here, we developed a nanosystem loaded with a near-infrared (NIR) agent to achieve chemo-photothermal combination therapy for inhibiting tumor growth and metastasis in TNBC. The NIR agent of ultrasmall sized copper sulfide nanodots with strong NIR light-absorbing capability, is entrapped into the doxorubicincontained temperature sensitive polymer-based nanosystem by a self-assembled method. The temperature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 47 publications
2
30
0
1
Order By: Relevance
“…[11,12] In addition, it has been observed that nanoparticle properties such as chemistry, size, shape, and aspect ratio all have an effect on pharmacokinetics, tumor penetration and organ accumulation. [13][14][15][16][17] These concepts have been reviewed in recent years due to the importance of achieving the appropriate trade-off between nanoparticle characteristics to achieve both prolonged circulation and good penetration into a solid tumor mass. [18][19][20] However, while there have been investigations of many nanoparticle sizes and shapes, there remain questions relating to how nanoparticles of specific sizes and architectures, but retaining the same surface chemistry behave in in vivo environments.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] In addition, it has been observed that nanoparticle properties such as chemistry, size, shape, and aspect ratio all have an effect on pharmacokinetics, tumor penetration and organ accumulation. [13][14][15][16][17] These concepts have been reviewed in recent years due to the importance of achieving the appropriate trade-off between nanoparticle characteristics to achieve both prolonged circulation and good penetration into a solid tumor mass. [18][19][20] However, while there have been investigations of many nanoparticle sizes and shapes, there remain questions relating to how nanoparticles of specific sizes and architectures, but retaining the same surface chemistry behave in in vivo environments.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the average sizes of MnO 2 in H 2 O 2 and GSH, decreased to 40.8 nm and 56.3 nm, respectively, indicating that the deposition of MnO 2 did not affect the structural integrity of CC. Previous studies have shown that nanoparticles in the range of 30-50 nm exhibit great tumor uptake and excellent penetration capability for poorly permeable tumors to achieve an improved antitumor effect 45 . Thus, the designed MnO 2 -coated nanoparticles (~120 nm) with the MnO 2 shell could be degraded after reacting with H 2 O 2 and GSH at the tumor site, which makes the particle size (~40 nm) decrease and reach the deep tumor more easily.…”
Section: Resultsmentioning
confidence: 99%
“…Most recent studies on penetrating nanoparticles are focused on reductions in particle size or charge reversal in response to TME-related factors (such as lower pH [199], hypoxia [200] and higher ROS level [201], rich GSH [202], and various enzymes [203][204][205]) or exogenous physical interventions (including laser irradiation [206], ultrasound [207], and thermal treatment [208]). Considering strategies to decrease the particle size, first is a complete nanocarrier with a smaller size, such as albumin [209], gold nanoparticles [202], nano-dots [208], and PAMAM [199], on which the cargo loading is easy. Thereafter, cross-linking of this nanocarrier together via various stimuli-responsive cleaved chemical bonds to generate a larger nanocarrier-aggregate with a suitable particle size of approximately 100-200 nm for long-term blood circulation, which could be dissociated into smaller drug-loaded segments on being triggered by certain stimuli at tumor sites, thereby achieving tumor penetration.…”
Section: Nanoparticle Penetrationmentioning
confidence: 99%